LEARNING AL-QUR'AN IN RUMAH QURAN: A CASE STUDY OF RUMAH QUR'AN BUNDA AISYAH - Nazih, Abdullah Ghulam (Spektra: Jurnal Ilmu-ilmu Sosial, 2019)
Al-Qur’an Al-Karim is teaching principle, because it includes Islamic teaching that organize the whole lives of muslims in all matters religion and the world. Islamic history records that Islam was very advanced in the education and learning model based on islamic civilization and based on Al-Qur’an. How important it is to learn Al-Qur’an for muslims. House of Qur’an as one of the facilities for studying the Qur’an for muslims. The methods of learning that are carried out in house of Qur’an are varied. The diversity of learning methods used in house of Qur’an also results in a variety of effectiveness and output. This research aims to describe the learning of the Al-Qur’an in house of Qur’an Bunda Aisyah. This research uses a case study reasearch using a qualitative approach with descriptive research metods. Learning in house of Qur’an Bunda Aisyah will be describe qualitatively. The results of this research indicate that by learning at House of Qur’an Bunda Aisyah, the Qur’an can easily be studied and learned by all ages, even though by elderly.